(untitled) (Journal of Medical & Health Sciences Review, 2025)
Iron deficiency anaemia (IDA) is a prevalent nutritional disorder characterized by inadequate iron availability, frequently resulting in impaired haemoglobin synthesis and reduced oxygen transport. Conventional iron supplementation, the primary treatment modality, is often associated with challenges such as poor patient compliance due to gastrointestinal side effects and suboptimal iron absorption, thus limiting its overall effectiveness. Recent evidence suggests that adjunctive therapies involving antioxidants, such as those abundantly found in pomegranate (Punica granatum), may offer a promising approach to enhance iron absorption, mitigate oxidative stress, and improve haematological parameters in anaemic patients. This study aimed to investigate the impact of pomegranate-derived antioxidants on key haematological parameters in patients diagnosed with IDA. A randomized, controlled trial (RCT) was conducted, involving 60 adult participants with confirmed IDA. Participants were randomly assigned to either the intervention group, receiving 250 mL of pomegranate juice daily in addition to standard oral iron therapy, or the control group, receiving oral iron therapy alone. The intervention period lasted for 8 weeks, with haematological parameters including haemoglobin levels, serum ferritin, and mean corpuscular volume measured at baseline, 4 weeks, and 8 weeks. The results of this study suggest that pomegranate-derived antioxidants may serve as a valuable adjunctive treatment strategy, potentially improving haematological outcomes in IDA patients compared to standard iron therapy alone. This highlights the potential of incorporating antioxidant-rich foods like pomegranate into the therapeutic regimen for IDA to improve overall patient outcomes. Further research is warranted to elucidate the underlying mechanisms and long-term benefits of this approach.